Pengaruh Employee Engagement dan Work Life Balance Terhadap Kinerja Pegawai pada Badan Perencanaan Pembangunan Daerah Kabupaten Lampung Selatan - Julio Cheppy Maulidi; Habiburahman Habiburahman; Haninun Haninun (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of employee engagement and work–life balance on employee performance at the Regional Development Planning Agency (Bappeda) of South Lampung Regency. This research employs a quantitative approach using a survey method. The population consists of all civil servant employees at Bappeda South Lampung Regency, totaling 66 respondents. A census sampling technique was applied, whereby the entire population was used as the research sample. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination. The results indicate that employee engagement has a positive and significant effect on employee performance, work–life balance also has a positive and significant effect on employee performance, and both variables simultaneously have a positive and significant effect on employee performance. The conclusion of this study indicates that employee performance at Bappeda South Lampung Regency is significantly influenced by employee engagement and work–life balance, both partially and simultaneously, demonstrating that improvements in these variables contribute to enhanced employee performance.